Tracheal stenosis due to endotracheal tube cuff hyperinflation: a preventable complication - Márcio Teodoro da Costa Gaspar; Linda Ferreira Maximiano; Hélio Minamoto; Jose Pinhata Otoch (University of São Paulo, 2019)
Endotracheal intubation injuries are rare, but may be devastating-mostly among the pediatric patients or when these occur in the distal trachea. Such complications typify a therapeutic challenge, which, besides requiring intellectual and technical resources, takes a long time to reach a resolution. The authors present the case of a 15-year-old girl admitted with an abnormal state of consciousness due to diabetic ketoacidosis. She was submitted to endotracheal intubation with hyperinflation of the tube cuff, which rendered tracheal necrosis and detachment of the tracheal mucosa, and consequent obstruction. Later, she developed scarring retraction and stenosis. The patient was successfully treated with an endotracheal prosthesis insertion. The aim of this report is to illustrate a preventable complication.